Analysis of Land Use Change from Forest to Agriculture and its Determinants: the Case of East Shewa, Oromia, Ethiopia - Ababu, Tesfanesh; Eyasu, Alemtsehay; Abebe, Mister; Negasa, Alemayehu; Girma, Gonche; Furo, Gemedo (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
The expansion of agricultural land through deforestation is becoming a serious problem in several regions of Ethiopia. The research was carried out in the Adami Tulu Jido Kombolcha district due to the observed expansion of agricultural land at the expense of forests. Therefore, this study aims to identify direct and indirect factors affecting land use and land cover change from forest to agriculture. Data was collected using household surveys, key informant interviews (KIIs), and focus group discussions (FGDs). Household surveys were conducted on 244 randomly selected households. Data were analyzed using descriptive statistics and the DPSIR framework to develop relationships between drivers, pressures, conditions, influences, and responses. The result shows that most farmers clear forests to expand their agricultural land. Further, the results showed that the proximate causes of the conversion of forest to agriculture were charcoal production, large-scale agriculture, and small-scale farming, as well as poverty, unemployment, and lack of enforcement of forestry laws, and weak forest policy were identified as the main indirect causes of agricultural land expansion at the expense of forests. In addition, the results indicate that the consequences of changing land use from forestry to agriculture are loss of biodiversity, increased soil erosion, floods and droughts, and shortages of wood, buildings, and fuel. The study results suggest that awareness-raising activities on the use of natural resources and the impacts of deforestation, as well as forest policies and strict enforcement of forestry laws, are important to establish and maintain appropriate use of land in that particular area.